Application of nanotechnology for the encapsulation of botanical insecticides for sustainable agriculture: Prospects and promises - Oliveira, Jhones Luiz de; Ramos Campos, Estefania Vangelie [UNESP]; Bakshi, Mansi; Abhilash, P. C.; Fraceto, Leonardo Fernandes [UNESP] (Elsevier B.V., 2014)
This review article discusses the use of nanotechnology in combination with botanical insecticides in order to develop systems for pest control in agriculture. The main types of botanical insecticides are described, together with different carrier systems and their potential uses. The botanical insecticides include those based on active principles isolated from plant extracts, as well as essential oils derived from certain plants. The advantages offered by the systems are highlighted, together with the main technological challenges that must be resolved prior to future implementation of the systems for agricultural pest control. The use of botanical insecticides associated with nanotechnology offers considerable potential for increasing agricultural productivity, while at the same time reducing impacts on the environment and human health.
Keywords: Biocides; Nanotechnology; Agriculture; Environmentally friendly